Islamic Education Curriculum Design Based on Sufism - Ciputri, Oki; Safitri , Oki; Panotogama , Muhammad Nurullah (Thawalib: Jurnal Kependidikan Islam, 2025)
The curriculum is like a spirit in learning, so it needs to be designed, implemented and evaluated to adjust to the times. The Islamic education curriculum needs to develop to meet needs. This study aims to determine the concept of the design of the Sufism-based Islamic education curriculum at the Pondok Pesantren Mahasiswa Jagad 'Alimussirry and its implementation. The type of research used is descriptive qualitative with a case study approach. The data collection techniques are through interviews, observations, and analysis of relevant documents. The results of this study indicate that the Sufism-based Religious education curriculum is very much needed to cultivate the spiritual aspects of students to balance the hegemony of the rationality aspect. A unique fact found is the implementation of the curriculum at the Jagad 'Alimussirry Islamic Boarding School which collaborates between the semester credit system and the tarekat system in the boarding school. Tarekat is the main part of the curriculum or compulsory courses that must be taken by all students. So that those who graduate from formal college also graduate from non-formal college and have carried out tarekat or spiritual journeys. Students who graduate from S1 will continue their S2 non-formally. By practicing this motto, it is hoped that the Jagad 'Alimussirry Islamic Boarding School students can get closer to Allah and achieve Allah's pleasure. Therefore, this study argues that Islamic education based on Sufism is a primary need to equip students in controlling themselves in the dynamics of life.